Large and constant coefficient of negative thermal expansion covering a wide temperature range in Zn1−xMnxNMn3 (0 ≤ x ≤ 0.3). (15th July 2018) - Lin, J.C.; Tong, P.; Tong, W.; Zou, Y.M.; Yang, C.; Zhu, F.; Zhang, X.K.; Li, L.F.; Wang, M.; Wu, Y.; Lin, S.; Song, W.H.; et al.
Abstract: The substitution of Mn for Zn was found to broaden the abnormal lattice shrinkage in Zn1− x Mn x NMn3 . When x  = 0.3, a large constant coefficient of negative thermal expansion (NTE) α L is found between 74 K and 150 K, which, though rare, is beneficial to practical applications of NTE materials. The magnetism studies indicate that the ferromagnetic clusters appear in the paramagnetic (PM) region and restrain the transformation from PM to antiferromagnetic (AFM), leading to the broadened NTE window. Moreover, the sample x  = 0.3 shows a linear PM-AFM transformation in the whole NTE window, resulting in the constant α L . Graphical abstract: Unlabelled Image